Myeloma Cells Are Highly Sensitive to the Granule Exocytosis Pathway Mediated by WT1-Specific Cytotoxic T Lymphocytes - Azuma, Taichi; Otsuki, Takemi; Kuzushima, Kiyotaka; Froelich, Christopher J.; Fujita, Shigeru; Yasukawa, Masaki (Clinical cancer research, 2004)
Purpose: Because WT1 is a universal tumor antigen, we examined the sensitivity of myeloma cells to WT1-specific cytotoxic T lymphocyte (CTL)-mediated cytotoxicity. Experimental Design: WT1 expression in hematologic malignant cells was examined by quantitative reverse transcription-polymerase chain reaction. The cytotoxicity of a WT1-specific CTL clone against hematologic malignant cells, including myeloma cells, was examined by standard chromium-51 release assays. The extent of membrane damage induced by purified perforin was examined. Induction of WT1-specific CTLs from the patients with multiple myeloma (MM) was attempted, and we examined their function against myeloma cells. Results: The expression levels of WT1 mRNA in myeloma and lymphoma cells were significantly lower than that in acute leukemia cells. Although the WT1 expression levels in myeloma and lymphoma cells were almost same, only myeloma cells were lysed efficiently by WT1-specific CTLs in a HLA-restricted manner. The amounts of interferon-γ produced by WT1-specific CTLs in response to stimulation with myeloma cells and with lymphoma cells were almost the same, suggesting that WT1 protein is processed and expressed in the context of HLA class I molecules similarly on both myeloma and lymphoma cells. The extent of membrane damage induced by purified perforin appeared to be significantly higher in myeloma cells than in lymphoma cells. WT1-specific CTLs appeared to be present in patients with MM. Conclusions: The present study has shown that susceptibility of membranes to perforin is an important factor determining the sensitivity of target cells to CTL-mediated cytotoxicity and that WT1 is an ideal target antigen for cellular immunotherapy of MM.